A Study to Assess the Effect of Chilled Cabbage Leaves Application on Breast Engorgement among Post-natal Mothers Admitted in Selected Hospital of Navi Mumbai - Salgaonkar, Rajashree (International Journal of Nursing Research, 2023)
Introduction: Breast engorgement is a common problem among post-natal women worldwide. Engorgement is a unpleasant, painful condition in which there is swelling and distension of the breasts usually in the early days of the initiation of lactation. Breast engorgement can be relieved by various non-pharmaceutical interventions. Chilled cabbage leaves usage is one of them. Aim: The present study was conducted to reduce the level of breast engorgement by the use of chilled cabbage leaves. Materials and Methods: A quasi-experimental design was used for this study. The study was performed on 40 post-natal mothers of the post-natal ward of a selected hospital, of Navi Mumbai. Storr scale (1988) used for assessing breast engorgement before and after the application of chilled cabbage leaves. Results: The study results show that there was a reduction in breast engorgement after the intervention and statistically verified. Conclusion: The analysis of data showed that using chilled cabbage leaves there is a significant reduction in breast engorgement.